Dune : Princess of Dune - Herbert, Brian; Anderson, Kevin J. (New York : Tor Publishing Group, 2023)
"Set two years before Dune: Princess of Dune is the never-before-told story of two key women in the life of Paul Muad'Dib-Princess Irulan, his wife in name only, and Paul's true love, the Fremen Chani. Both women become central to Paul's galaxy-spanning Imperial reign. Raised in the Imperial court and born to be a political bargaining chip, Irulan was sent at an early age to be trained as a Bene Gesserit Sister. As Princess Royal, she also learned important lessons from her father-the Padishah Emperor Shaddam Corrino IV. Now of marriageable age, Princess Irulan sees the machinations of the many factions vying for power-the Bene Gesserit Sisterhood, the Spacing Guild, the Imperial throne, and a ruthless rebellion in the Imperial military. The young woman has a wise and independent streak and is determined to become much more than a pawn to be moved about on anyone's gameboard. Meanwhile, on Arrakis, Chani-the daughter of Liet-Kynes, the Imperial Planetologist who serves under the harsh rule of House Harkonnen-is trained in the Fremen mystical ways by an ancient Reverend Mother. Brought up to believe in her father's ecological dream of a green Arrakis, she follows Liet around to Imperial testing stations, surviving the many hazards of desert life. Chani soon learns the harsh cost of Fremen dreams and obligations under the oppressive boot heel of the long Harkonnen occupation"--
Keywords: Dune (Imaginary place) -- Fiction; Princesses -- Fiction; Science fiction; Novels